First report of two rapid-onset fatal infections caused by a newly emerging hypervirulent K. Pneumonia ST86 strain of serotype K2 in China - Zhang, Yibo; Sun, Jingyong; Mi, Chenrong; Li, Wenhui; Zhao, Shengyuan; Wang, Qun; Shi, Dake; Liu, Luo; Ding, Bingyu; Chang, Yung-Fu; Guo, Hongxiong; Guo, XiaoKui; et al. (Frontiers in Microbiology, 2015)
Here, we present the first report of one suspected dead case and two confirmed rapid-onset fatal infections caused by a newly emerging hypervirulent Klebsiella pneumoniae ST86 strain of serotype K2. The three cases occurred in a surgery ward during 2013 in Shanghai, China. A combination of multilocus sequence typing, pulsed-field gel electrophoresis, phenotypic and PCR tests for detecting virulence factors (VFs) was used to identify the isolates as K2 ST86 strains with common VFs, including aerobactin and rmpA. Furthermore, the two K2 ST86 strains additionally harbored a distinct VF kfu (responsible for iron uptake system), which commonly existed in invasive K1 strains only. Thus, the unusual presence of both K1 and K2 VFs in the lethal ST86 strain might further enhance its hypervirulence and cause rapid onset of a life-threatening infection. Nevertheless, despite the administration of a combined antibiotic treatment, these three patients all died within 24 hours of acute onset, thereby highlighting that the importance of early diagnosis to determine whether the ST86 strains harbor key K2 VF and unusual K1 kfu and whether patients should receive a timely and targeted antibiotic therapy to prevent ST86 induced fatal pneumonia. Finally, even though these patients are clinically improved, keeping on with oral antibiotic treatment for additional 2-3 weeks will be also vital for successfully preventing hvKP reinfection or relapse.